A Comparative Qualitative Study of Misconceptions Associated with Contraceptive Use in Southern and Northern Ghana - Adongo, Philip B.; Tabong, Philip T.-N.; Azongo, Thomas B.; Phillips, James F.; Sheff, Mallory C.; Stone, Allison E.; Tapsoba, Placide (Frontiers in Public Health, 2014)
Evidence from Ghana consistently shows that unmet need for contraception is pervasive with many possible causes, yet how these may differ by cultural zone remains poorly understood. This qualitative study was designed to elicit information on the nature and form of misconceptions associated with contraceptive use among northern and southern Ghanaians. Twenty-two focus group discussions (FGDs) with married community members were carried out. Community health officers, community health volunteers, and health care managers were also interviewed using a semi-structured interview guide. FGDs and in-depth interviews were recorded digitally, transcribed verbatim, and analyzed using QSR Nvivo 10 to compare contraceptive misconceptions in northern and southern Ghana. Results indicate that misconceptions associated with the use of contraceptives were widespread but similar in both settings. Contraceptives were perceived to predispose women to both primary and secondary infertility, uterine fibroids, and cancers. As regular menstrual flow was believed to prevent uterine fibroids, contraceptive use-related amenorrhea was thought to render acceptors vulnerable to uterine fibroids as well as cervical and breast cancers. Contraceptive acceptors were stigmatized and ridiculed as promiscuous. Among northern respondents, condom use was generally perceived to inhibit erection and therefore capable of inducing male impotence, while in southern Ghana, condom use was believed to reduce sensation and sexual gratification. The study indicates that misconceptions associated with contraceptive use are widespread in both regions. Moreover, despite profound social and contextual differences that distinguish northern and southern Ghanaians, prevailing fears and misconceptions are shared by respondents from both settings. Findings attest to the need for improved communication to provide accurate information for dispelling these misconceptions.